One-Year Stability of the Devereux Early Childhood Assessment for Preschoolers, Second Edition. (December 2018) - Carlson, John S.; Voris, Dylan S. T.
The Devereux Early Childhood Assessment (DECA) and recently updated Devereux Early Childhood Assessment for Preschoolers, Second Edition (DECA-P2) are strength-based measures that can inform early intervention. Whereas the short-term psychometric properties of these parent rating scales are strong, little is known about their long-term stability. Study findings from a diverse Head Start sample ( N = 282, DECA; N = 346, DECA-P2) revealed 12-month, test–retest reliability of protective factors ( r = .65) to be equivalent on the DECA-P2 and the DECA. The stability of parent ratings of behavior concerns appears improved in the newer edition ( r = .53 vs. r = .46). Additional consideration should be given to the stability of the DECA-P2 and its use as short- and long-term social, emotional, and behavioral intervention progress monitoring tool.